Solve the qudaratic equation by factorization x^2+x-(a+1)(a+2)=0

Suman Cole 2020-10-20 Answered
Solve the qudaratic equation by factorization
x2+x(a+1)(a+2)=0
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Expert Answer

Liyana Mansell
Answered 2020-10-21 Author has 97 answers
Step 1
Given:
x2+x(a+1)(a+2)=0
Step 2
x2+x(a+1)(a+2)=0
x2=x(a+2)x(a+1)(a+1)(a+2)=0
x(x+a+2)(a+1)(x+a+2)=0
(xa1)(x+a+2)=0
xa1=0 and x+a+2=0
x=a+1,a2
Not exactly what you’re looking for?
Ask My Question

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more